String effects in the Wilson loop: a high precision numerical test - Caselle, M.; Fiorentini, Raffaele; Gliozzi, F.; Hasenbusch, Martin; Provero, P. (Nuclear physics. B, Particle physics, 1997)
We test numerically the effective string description of the infrared limit of lattice gauge theories in the confining regime. We consider the 3D Z2 lattice gauge theory, and we define ratios of Wilson loops such that the predictions of the effective string theory do not contain any adjustable parameters. In this way we are able to obtain a degree of accuracy high enough to show unambiguously that the flux-tube fluctuations are described, in the infrared limit, by an effective bosonic string theory.
Elektronische Reproduktion der Druck-Ausgabe
Available online 19 May 1998
Gesehen am 06.07.2022